The biomechanical strength of olecranon fixation constructs: a systematic review and meta-regression - Cutter, Brenden; Kelly, Shayne R.; Beckett, Charles R.; Huish, Eric G. (International Journal of Research in Orthopaedics, 2022)
Olecranon fractures are often operative when displaced over 2 mm, but the most stable fixation construct is debated. The purpose of this study was to provide an overview of biomechanical properties of the most commonly used surgical fixations of olecranon fractures. This systematic review included 13 biomechanical studies comparing displacement during cyclic loading of olecranon fractures fixated with either tension band wiring (TBW), intramedullary screw, or plate fixation. In regard to overall gapping, plates displayed (and screws trended towards) increased stability versus TBW. However, there was no difference between the constructs in gapping at the articular surface. Plating displayed increased stability along the posterior surface. No construct allowed gapping over 2 mm, suggesting safe early post-operative motion with any of the techniques.